The US-China tech war: Where does Turkey stand? - Çağdaş Üngör (Stiftung Wissenschaft und Politik (SWP), 2025)
The techno-geopolitical rivalry between China and the United States has intensified in recent years. Turkey's souring relations with the US over the past decade has prevented the former from reaping the spoils of the Sino-US tech war as an American ally. Ankara has its own ambitions in the so-called Fourth Industrial Revolution and is prioritising gaining access to advanced technology under affordable price arrangements in which Chinese tech companies offer important opportunities. Since Turkey is a NATO member and an EU candidate, its incremental move towards China's technology ecosystem should be of concern to EU decision-makers. Brussels should promote policies to foster collaboration with Turkey so that today's geoeconomic challenges can be tackled together.
Keywords: 320; techno-geopolitical rivalry; China; United States; Turkey; Fourth Industrial Revolution; EU; NATO; geoeconomic challenges; AI; 5G; semiconductor value chain; Xiaomi; Huawei; DeepSeek; ChatGPT